Physiological potential of sorghum seeds under discontinuous hydration and water deficiency conditions (Revista Ciência Agronômica, 2020)
Hydration and dehydration cycles during imbibition of seeds may influence their physiological performance,making them more vigorous and resistant to abiotic factors such as water stress. The aim was to investigate whether the timesand discontinued hydration cycles condition higher tolerance to water deficiency conditions in germination and seed vigorand accumulation of organic compounds in sorghum seedlings. The experiment was carried out in a randomized experimentaldesign with four replicates of 50 seeds. The treatments were arranged in a 3 × 4 × 6 factorial scheme (hydration times, hydrationand dehydration cycles, osmotic potentials). The imbibition curve of the species was determined based on three times (X, Y andZ); and the dehydration curve was constructed. With these times, the seeds were submitted to 0, 1, 2 and 3 cycles of hydrationand dehydration (HD). Then, they were submitted to germination test on paper moistened with polyethylene glycol 6000solution at the osmotic potentials of 0.0 (distilled water), -0.2, -0.4, -0.6, -0.8 and -1.0 MPa. Germination and vigor of sorghumseeds are severely impaired in water potentials equal to or greater than -0.4 MPa. Application of three cycles of hydration anddehydration for a period of 13h in sorghum seeds improves tolerance to water deficiency conditions during germination andseedling development, and provides greater contents of soluble N-amino content and total soluble carbohydrates.